The Role of Government Expenditure on Per Capita Income Convergence in East Java Province - Hardianto, Erwin; Solihin, Achmad (Jurnal Ilmu Ekonomi Terapan, 2024)
This research aims to test and analyze the absolute and conditional convergence of per capita income from 38 districts/cities in East Java with the variables PAD, BOS and BOK during the period 2020 - 2022. According to the Chow, Hausmann test and Lagrange Multiplier, the panel data convergence model estimates using the fixed effect model method. Results show that in the districts/cities and observation period, divergent conditions occurred. Also, conditional variables did not have a significant influence on the growth of per capita income. This condition can occur because capital and technology are distributed unevenly between districts/cities. The implication of this research is to improve the allocation and distribution of the government budget, especially those related to School Operational Assistance (BOS) and Health Operational Assistance (BOK).